Placing Perceptions of Unsafety: Examining Spatial Concentrations and Temporal Patterns of Unsafe Locations at Micro-Places - Kronkvist, Karl (Journal of quantitative criminology, 2024)
Objectives To explore the extent to which unsafe locations are concentrated to micro-places within the city of Malmö, Sweden, and whether there is a temporal stability in these micro-places over time. Methods Information on unsafe locations is obtained from an open-ended item across three waves of a random sample community survey. Reported unsafe locations are geocoded as polygon, polyline, and point features and merged with a 200 by 200-m grid-cell network using both unadjusted and weighted counts. Results The results suggest that unsafe locations are concentrated to a small share of grid-cells using different metrics. There are also signs of spatial clustering and a temporal stability of unsafe locations over time. Conclusions As unsafe locations are concentrated to a small share of micro-places the results have important implications for both theory and practice. However, further research exploring unsafety and fear of crime at micro-places is highly warranted.